Sistem Informasi Perpustakaan Pada Universitas Mahaputra Muhammad Yamin - Fendri Adi Saputra; Ella Yedia Fitri (Ikatan Ahli Informatika Indonesia, 2020)
As the development of increasingly sophisticated information technology and the existence of these developments will make it easier for human work, including accessing various information very quickly and accurately. As one of the convenience in accessing information is the emergence of various kinds of information about the field of aspen to be informed, one of which is the library information system. With the library system, a person can access wherever and whenever information about the library such as information about books in the library is quite easy for someone to access library information. One of the libraries that has implemented library information systems is the library at Mahaputra Muhammad Yamin University where the library has implemented a web-based information system but there are still many deficiencies so that the system that is implemented has not given the maximum so it is less efficient to be able to see the deficiencies that exist in Mahaputra Muhammad Yamin University's information system can be seen from the old Asians that are applied to the Mahaputra Muhammad Yamin University's library information system.